Logistics information support - Нurzhii Natalia; Bakhmetova, Yana; Halchynska, Iryna (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. Analyzed different approaches to the defi nition of hypertext, and highlights the main stages in the development of hypertext technology. Are considered key features and benefi ts of hypertext documents in comparison with traditional formats of information Design/methodology/approach. The basic principles of the research are systematic and comparative methods, institutional and structural-functional approaches have been used. Findings. The article reveals the importance of information provision in logistics. Logistics is currently considered a significant moment in events aimed at increasing the financial efficiency of production. The improvement of the functioning of the information-logistic system is achieved by the method of the greatest coordination of material and information flows at their connection, which in turn is considered one of the main tasks of logistics. In order for the task to be performed, it is necessary to use electronic data processing, standardization of logistics, organization of work should be based on multifunctional analysis and structuring. In addition, it is necessary to use new technologies that facilitate automation of operations. The urgency of the problems associated with the formation of the global information economy plays an important role, as modern organizations need a qualitatively new economic resource that will contribute to sustainable growth. Information economy differs from all previous types of economy by the fact that the most important productive resource here is not physical good, but something elusive - information. The most important importance in the information economy becomes the task of managing information resources at different levels of the hierarchy. Solving this problem allows information logistics to systematize a set of measures aimed at managing the production of information, its movement and marketing with minimal cost. In the article the main concepts of information logistics, peculiarities of construction and functioning of the information system that provide the functioning of processes are considered. Since the information logistics system is a complex integrated system that organizes the accounting, control, planning, procurement, supply, distribution of material and technical resources, then the article considers the main features of logistics systems. Achieving logistics goals requires continuous monitoring and management of information flows. It is emphasized on the need to take into account the space-time relationships between logistic data. To account for all these conditions, integrated integrated information systems must be applied. Consider the example of MK Zaporizhstal, which successfully implemented the QR system and optimized the logistics processes in the enterprise. Research limitations/implications. The paper clearly provides states the action of enterprises in crisis situations. Originality/value. In a unique way, information, being a resource for managing a controlled product, transferring information to an informational formor (koristuvacha). Interaction between them is assigned to information flow, which is formed in information protection. At the center of the material abo financial flow, the responsibility of the author is competent, competent, competent, and competent. Information is shown in all problems of the current financial and material flows, the permission of the controller and the control of actions. For the organization of the effective logistic system, it is necessary to see and optimize all the business processes of the organization, to conduct their reengineering, to allow the political process to manage the logic. On chol_ vsіkh tsikh re-establishment to stand informacіyn processes.